2013
DOI: 10.1088/0004-637x/778/1/41
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enhanced Stratification on Equatorward Dynamo Wave Propagation

Abstract: We present results from simulations of rotating magnetized turbulent convection in spherical wedge geometry representing parts of the latitudinal and longitudinal extents of a star. Here we consider a set of runs for which the density stratification is varied, keeping the Reynolds and Coriolis numbers at similar values. In the case of weak stratification, we find quasi-steady dynamo solutions for moderate rotation and oscillatory ones with poleward migration of activity belts for more rapid rotation. For stron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
205
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(237 citation statements)
references
References 95 publications
(150 reference statements)
28
205
1
Order By: Relevance
“…The current helicity can in principle reverse the sign of the scalar α-effect (Warnecke et al 2014). For instance, it has recently been shown that the direction of the propagation of the magnetic field through a cycle can depend upon the Parker-Yoshimura mechanism (e.g., Racine et al 2011;Käpylä et al 2013;Warnecke et al 2014).…”
Section: Kinematic Versus Nonlinear Dynamo Wavesmentioning
confidence: 99%
“…The current helicity can in principle reverse the sign of the scalar α-effect (Warnecke et al 2014). For instance, it has recently been shown that the direction of the propagation of the magnetic field through a cycle can depend upon the Parker-Yoshimura mechanism (e.g., Racine et al 2011;Käpylä et al 2013;Warnecke et al 2014).…”
Section: Kinematic Versus Nonlinear Dynamo Wavesmentioning
confidence: 99%
“…We solve the hydromagnetic equations in a cubic domain of size 2 . 3 ( ) p To connect with spherical geometry, we can imagine our simulation box being located in the northern hemisphere of the Sun such that the x axis corresponds to the radially outward direction, the y axis to the toroidal direction, and the z axis to the direction of increasing latitude; see, e.g., Käpylä et al (2013), who used the same correspondence in their Section3.6. Within this framework, the momentum, continuity, and induction equations become…”
Section: Modelmentioning
confidence: 99%
“…Moreover, our simple model then avoids the vastly different time and length scales of global and local dynamos in realistic settings. Capturing them within a single model remains a challenging task in global convection simulations (Vögler et al 2005;Käpylä et al 2013;Hotta et al 2015;Karak et al 2015a). In the present paper, our aim is to address the basic question of whether and how the small-scale magnetic field is correlated with the dynamo cycle in a simple realization of a turbulent dynamo that combines the physics of a small-scale dynamo with that of an aW dynamo.…”
Section: Introductionmentioning
confidence: 99%
“…These simulations are also able to reproduce the equatorward migration of the toroidal field as observed in the Sun. The magnetic field is strongest in the middle of the convection zone and propagates from there both toward the surface and the bottom of the convection zone (Käpylä et al 2013). Furthermore, found that the equatorward migration occurring in their global simulations of self-consistent convectively driven dynamos can be explained entirely by the Parker-Yoshimura rule (Parker 1955a;Yoshimura 1975) of a propagating α Ω dynamo wave, where α is related to the kinetic helicity and Ω is the local rotation rate of the Sun.…”
Section: Introductionmentioning
confidence: 97%